The boundless sea - Horden, Peregrine, author.
1 online resource.
Keywords: "This volume brings together for the first time a collection of twelve articles written both jointly and individually by Peregrine Horden and Nicholas Purcell as they have participated in the debates generated by their major work, The Corrupting Sea: A Study of Mediterranean History (2000). One theme in those debates has been how a comprehensive Mediterranean history can be written: how an approach to Mediterranean history by way of its ecologies and the communications between them can be joined up with more mainstream forms of enquiry - cultural, social, economic, and political, with their specific chronologies and turning points. The second theme raises the question of how Mediterranean history can be fitted into a larger, indeed global history. It concerns the definition of the Mediterranean in space, the way to characterise its frontiers, and the relations between the region so defined and the other large spaces, many of them oceans, to which historians have increasingly turned for novel disciplinary-cum-geographical units of study. A volume collecting the two authors' studies on both these themes, as well as their reply to critics of The Corrupting Sea, should prove invaluable to students and scholars from a number of disciplines: ancient, medieval and early modern history, archaeology, and social anthropology"--